Perspectivas da agricultura sustentável no Brasil - Rosângela Ap. de Medeiros Hespanhol (Confins)
The process of technological incorporation happened in the agriculture along the history and, more precisely, the diffusion of the Green Revolution package after Second World War produced several socio-environmental implications. With the aggravation of those problems in world scale and, above all countries as Brazil, there was the incorporation, still limited, of environmental concerns related to the agriculture. That change fomented the discussion and leaded it to the formulation of analysis perspectives and to the formulation of antagonistic and conflicting intervention amongst themselves, reflecting different interests and opinions about the models of the countries development and their own sustainability. It was tried to identify two of these perspectives in Brazil: the one that still conceives the scientific-technological development as the only road capable to solve the derived problems of the shortage of foods and the exhaustion of the natural resources; and those that are opposed to this perspective. They propose more maintainable forms, which could be joined under the Alternative Agriculture denomination. It was also tried to discuss the challenges and the perspectives that come in terms of viability terms to discuss and of expansion of the maintainable production systems in environmental and social terms in the agriculture of small scale in Brazil, to example of the organic production.